Studies On Broodstock Nutrition Of Malaysian Freshwater Giant Prawn Macrobrachium Rosenbergii (De Man) - Das, Nitya Nanda (1995)

(untitled)
A study of the essential amino acid constraints of diets based on the egg essential amino acid content of broodstock of M. rosenbergii (de Man) was conducted using a linear interactive and discrete optimizer software in least cost feed formulation for the broodstock. Four experiments using different formulation of diets under different environmental conditions were conducted and the following results were obtained: In the first experiment three types of isocaloric (400 kca1/100 g diet) formulated diets having 30% protein (P30), 40% protein (P40) and 50% protein (P50) along with a commercial control diet (30% protein with gross energy 446 kca1/100 g diet) were used to determine their suitability as feed for M. rosenbergii brood stock. The fecundity of prawns fed diet P30 and P40 were not significantly different (P>O .05) but were significantly different from prawns fed P50 and the control diet (P<0.05). The experimental diet P40 (with P:GE ratio of 99.33) was numerically superior to diets with P30 or P50 in terms of prawns fecundity ( 1 354.20 eggs/g body weight) and hatching rate (86.42%).